Combating sharenting: Interventions to alter parents' attitudes toward posting about their children online. (December 2021) - Williams-Ceci, Sterling; Grose, Gillian E.; Pinch, Annika C.; Kizilcec, Rene F.; Lewis, Neil A.
Abstract: Sharenting is a recent phenomenon in which parents disclose detailed information about their children online, which can risk their children's long-term safety and parental relationships. To mitigate these risks and discourage the sharing of inappropriate content, we developed and tested two interventions to deter sharenting in a randomized controlled experiment with 246 parents. Parents watched a video about the dangers of sharenting (Intervention 1) with some assigned to write a summary of this video (Intervention 2) while the remaining participants watched a video unrelated to sharenting (Control). We found that the intervention reduced parents' willingness to post both inappropriate and appropriate content about children, but only if parents reflected on the video message in writing. The interventions did not, however, change parents' attitudes about asking their children for permission before posting. The results advance our understanding of sharenting and offer insights about potential brief and scalable approaches to mitigate sharenting and its consequences. In particular, we demonstrate that a purely informational intervention is not as effective as one that encourages substantive reflection. Highlights: Sharenting, when parents post detailedly about their children online, has risks if done inappropriately. We tested two interventions (a video with and without a summarization task) intended to change attitudes toward sharenting. The video with summary intervention made attitudes more negative toward inappropriate and appropriate sharenting. Neither intervention affected the perceived importance of asking children's permission before sharenting.